Ultrasonic-assisted extraction of polyphenols and antioxidants from Picea abies bark - Chmelová, Daniela; Škulcová, Dominika; Legerská, Barbora; Horník, Miroslav; Ondrejovič, Miroslav (Journal of biotechnology, 2020)
•Optimal conditions for the maximal AC and TPC was determined for UAE.•The maximum AC and TPC were reached in 2-times shorter extraction time by UAE.•Significant correlation was observed between AC and TPC.•The presence of some phenolic acids was confirmed.•Both types of extraction were best described by Peleg’s and Patricelli’s models. Spruce bark represents a reservoir of bioactive compounds. The aim of this study was to investigate the effect of independent variables (temperature, liquid to solid ratio, time and methanol content) and their interaction within the extraction process by the response surface methodology (RSM). The effect of conventional (solvent extraction; SE) and modern (ultrasound-assisted extraction; UAE) methods for the extraction of antioxidants (antioxidant capacity; AC) and polyphenols (total polyphenol content; TPC) was compared. Maximum yields of AC and TPC by SE and UAE were obtained at modified optimal conditions of 63 °C, methanol content of 53 % (v/v) and 38 mL of extraction solvent per gram of dry material. Two-step extraction process consisting of the fast washing and slow diffusion steps was suitable described by Peleg and Patricelli mathematic models. The HPLC fingerprints of both extracts did not show significant differences while the content of phenolic compounds extracted by UAE was 1.1- to 7.1-times higher than that obtained by SE, quantified by HPLC.